School of Charm - Scott, Lisa Ann (Katherine Tegen Books, an imprint of HarperCollins Publishers, 2014)
After her beloved father's death in 1977, eleven-year-old tomboy Chip tries to fit with her family of beauty queens, making unlikely new friends at Miss Vernie's unusual charm school in Mt. Airy, North Carolina.